Morphological variations of the mandibular canal in digital panoramic radiographs: a retrospective study in a Chilean population - Fuentes, Ramón; Arias, Alain; Farfán, Constanza; Astete, Nicolás; Garay, Ivonne; Navarro, P.; Dias, Fernando José
Background: Morphological variations of the mandibular canal (MC) have been described in literature, so the clinician must be able to recognise them and adapt their treatment accordingly. The aim of this study was to determine the prevalence of morphological variations of the MC using digital panoramic radiographs (DPR) of Chilean patients. Materials and methods: A retrospective study in which 1400 DPR were analysed to identify cases of bifid, trifid and retromolar MC. The radiographs were analysed independently by two examiners who had previously been trained by a specialist in oral and maxillofacial radiology. Inclusion and exclusion criteria were applied to reach a final sample. Results: Nine hundred and twenty-five radiographs were included (599 female, 326 male; mean age 36.1 ± 15.54 years). The prevalence of bifid MC was 11% (n = 102), with no significant differences by sex (p = 0.069). Proportion of bifid MC was higher among younger patients (p = 0.038). Prevalence of morphological variations of type 1 bifid MC was 7.4% (n = 69), type 2 was 2.3% (n = 23), type 3 was 0% (n = 0) and type 4 was 1.1% (n = 10). Prevalence of retromolar canal was 0.9% (n = 8), with no significant differences by sex (p = 0.893) or age (p = 0.371); of these, 2 (0.2%) cases were forward type and 6 (0.6%) cases were retromolar type. No cases of trifid MC were found. Conclusions: Digital panoramic radiographs are useful for detecting morphological variations of the MC; we were able to identify three types of bifid MC as well as retromolar canals. Proper identification of these variations by an easily accessible examination is important for avoiding possible complications in clinical-surgical practice